Is aluminum (Al) eliminated by senescent structures of Miconia albicans, an Al-accumulating species from Brazilian savanna? - Timpone, Luá Taibo [UNESP]; Habermann, Gustavo [UNESP] (Elsevier, 2022)
Aluminum (Al)-accumulating plants are distributed worldwide. In the Cerrado vegetation in South America, these plants occur as few woody species from Melastomataceae, Rubiaceae, Syplocaceae and Vochysiaceae. Nevertheless, Al assessments are usually limited to their leaves. In this field study, we measured the Al concentration in different vegetative and reproductive structures of Miconia albicans (Sw.) Triana (Melastomataceae) with a special emphasis on changes of Al accumulation in senescent organs and tissues. We collected leaf (leaf bud, two young leaf phases and senescent leaf), wood, bark, root, inflorescence (raceme, flower bud and flower) and fruit (two initial fruit phases, unripe and ripe fruit) to evaluate the Al distribution within the whole plant. The mature leaf was separated into leaf blade and veins, and the former accumulated more Al in relation to leaf veins, following the same pattern observed for Vochysiaceae Al-accumulating plants. Senescent leaf and bark accumulated more Al than mature leaves, and as flowers developed into ripe fruits the Al concentration decreased. Aluminum accumulation is not limited to the leaves of M. albicans, and the greater Al accumulation in senescent leaves and bark suggests that this Al-accumulating species uses senescent leaves and bark to eliminate Al from the plant.
Keywords: Al3+; Bark; Cerrado; Inflorescence; Melastomataceae; Root